Thermal properties of Inconel 625-NbC metal matrix composites (MMC) - Adrian Graboś; Paweł Rutkowski; Jan Huebner; Paweł Nieroda; Dariusz Kata; Shigenari Hayashi (Materials & Design, 2022)
Inconel 625-NbC Metal Matrix Composite (MMC) is an emergent material of Inconel 625-carbide composites. It is characterized by dense microstructure, improved hardness, and preserved passive Cr-rich layer formation during oxidation. In this study, its thermal properties were investigated. Inconel 625-NbC composites and Inconel 625 reference alloy were consolidated by Spark Plasma Sintering (SPS). Their microstructure, phase composition, Coefficient of Thermal Expansion (CTE), thermal diffusivity (α), thermal conductivity (λ), and specific heat (cp) were studied. The addition of NbC into Inconel 625 matrix did not significantly affect the CTE or λ of the final composite. Thermal conductivity of Inconel 625-NbC was initially lower than 625 superalloy but was increasing faster in function of temperature. cp functions of SPS-ed 625 alloy and composites had different slopes in comparison to literature. The influence of hot rolling, part of Inconel 625-NbC obtaining SPS technology, was also studied. It affected composites cp.